2019
DOI: 10.1002/jmri.26648
|View full text |Cite
|
Sign up to set email alerts
|

Association of distant recurrence‐free survival with algorithmically extracted MRI characteristics in breast cancer

Abstract: Background While important in diagnosis of breast cancer, the scientific assessment of the role of imaging in prognosis of outcomes and treatment planning is limited. Purpose: To evaluate the potential of using quantitative imaging variables for stratifying risk of distant recurrence in breast cancer patients. Study Type Retrospective. Population In all, 892 female invasive breast cancer patients. Sequence Dynamic contrast‐enhanced MRI with field strength 1.5 T and 3 T. Assessment Computer vision algorithms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Kurtosis, selected from one of the first-order features, was negatively associated with the risk of disease in this study. Many recent studies have particularly emphasized the significance of Kurtosis in colorectal, pancreatic, and breast cancers ( 16 , 32 , 33 ). The large area emphasis belongs to one of the features of GLSZM and is very suitable for quantifying the texture and heterogeneity of tumors because it considers the interaction between adjacent pixels ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kurtosis, selected from one of the first-order features, was negatively associated with the risk of disease in this study. Many recent studies have particularly emphasized the significance of Kurtosis in colorectal, pancreatic, and breast cancers ( 16 , 32 , 33 ). The large area emphasis belongs to one of the features of GLSZM and is very suitable for quantifying the texture and heterogeneity of tumors because it considers the interaction between adjacent pixels ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…MajorAxisLength was found to associate with distant recurrence-free survival in Breast Cancer. 37 Inertia was significantly correlated with fibroblast growth factor receptor (FGFR) in head and neck squamous cell carcinoma. 38 A study exploring wavelet-based short-run high gray-level emphasis found that the short-run high gray-level emphasis achieved high accuracy in the classification between benign and malignant masses, suggesting that radiomics features extracted from MRI are highly correlated with ovarian epithelial cancer classification and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [20] also found that tumors with a high risk of recurrence, based on ODX results, correlated with the enhancement texture, according to the maximum enhancing voxels within a lesion. Mazurowski et al [41] investigated the association of distant recurrence-free survival with MRI characteristics in breast cancer, and found the strongest associations with distant recurrence-free survival were signal enhancement ratio partial tumor volume, kurtosis of the signal enhancement ratio map within tumor and the other quantitative data. Assessment of heterogeneity, including skewness and kurtosis, may be important for deciding treatment options for breast cancer patients and for predicting recurrence prognosis.…”
Section: Discussionmentioning
confidence: 99%